Open Domain Collaborative Storytelling with Say Anything - Swanson, Reid; Gordon, Andrew (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
In this demonstration we present Say Anything, an open domain interactive storytelling application where an author’s original story sentences are used to select subsequent sentences from a corpus of millions of stories extracted from Internet weblogs.